Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. Kencana Sawit Indonesia di Kabupaten Solok Selatan - Sisi Purnama Sari; Zusmawati Zusmawati (Lembaga Yasin AlSys, 2026)
Although employee job satisfaction has been widely studied, research that specifically examines the influence of leadership style and work environment in plantation companies remains limited. This study aims to analyze the influence of leadership style and work environment on employee job satisfaction at PT Kencana Sawit Indonesia. This study used a quantitative approach with a survey design, involving 109 respondents selected using total sampling. Data were collected using a questionnaire and analyzed through multiple linear regression. The results showed that leadership style had a positive and significant effect on employee job satisfaction. The work environment also had a positive and significant effect on employee job satisfaction. These findings contribute to the development of human resource management studies and expand understanding of the factors that influence employee job satisfaction in the plantation sector. The conclusion of this study confirms that leadership style and work environment play an important role in improving employee job satisfaction. Its practical implication is that management needs to apply participatory leadership and create a conducive work environment to support employee job satisfaction at PT Kencana Sawit Indonesia.